The Rat Plasminogen System, Intrahepatic Fibrinolysis and Carbon Tetrachloride Hepatotoxicity - Innerfield, I; Rowley, G. R; Zweil, P; Porpora, J (Thrombosis and Haemostasis, 1967)
Carbon tetrachloride hepatotoxicity in rats is significantly reduced by small doses of orally given enzymes which activate the rat plasminogen system. Enzymes incapable of activating rat plasminogen are ineffective. The suggestion is made that the liver protection afforded by small doses of SK or trypsin relates to the pro-coagulant, permeability-decreasing, anti-edema action of suitably low doses of SK or trypsin.